The role of Mincle in innate immune to fungal keratitis - Zhao, Guiqiu; Xu, Qiang; Lin, Jing; Chen, Wenjun; Cui, Tingting; Hu, Liting; Jiang, Nan (The Journal of Infection in Developing Countries, 2017)
Introduction: This study aimed to detect the early expression of macrophage-inducible C-type lectin (Mincle) and investigate its role in the innate immune response of fungal keratitis (FK). Methodology: Wistar rats were used to make fungal keratitis models. The inflammatory responses and corneal lesions were observed by slit-lamp microscope.RT-PCR, immunohistochemistry, and immunofluorescence were used to detect the expression of Mincle in the rat corneal epithelium. The expression of eight cytokines (CXCL1, CXCL2, IL-1β, IL-6, IL-10, TNF-α, CCL2, CCL3) were detected by real-time RT-PCR and immunohistochemistry. Lastly, corneal epithelium of 54 patients with Aspergillus fumigatus keratitis and 13 ocular trauma patients were collected to detect expression of Mincle by real-time RT-PCR, and 12 FK and 10 ocular trauma paraffin samples were collected to confirm expression of Mincle by immunohistochemistry. Results: The expression of Mincle was significantly upregulated at 4, 8, 16, and 24 hours after fungal infection. There were significant differences in the expression of the eight inflammatory cytokines between the blank control group and the fungus-infected group. Mincle expression was correlated with the expression of TNF-a, IL-1β, IL-10, and CCL3 in the cornea. The mRNA expressions of Mincle in the corneas of both normal and FK patients were significantly different. Conclusions: The expression of Mincle increases significantly during the early period of Aspergillus fumigatus infection, while expression of eight corresponding cytokines changes. Mincle, as a pattern recognition receptor, may play a role in the early innate immune response of the corneal resistance against fungus.